Capitalism in the age of globalization: the management of contemporary society - "Amin, Samir" (Delhi, 1997)
Samir Amin remains one of the world's most influential thinkers about the changing nature of North-South relations in the development of contemporary capitalism. In this highly prescient book, originally published in 1997, he provides a powerful analysis of the new unilateral capitalist era following the collapse of the Soviet model, and the apparent triumph of the market and globalization. Amin's innovative analysis charts the rise of ethnicity and fundamentalism as consequences of the failure of ruling classes in the South to counter the exploitative terms of globalization. This has had profound implications and continues to resonate today. Furthermore, his deconstruction of the Bretton Woods institutions as managerial mechanisms which protect the profitability of capital provides an important insight into the continued difficulties in reforming them. Amin's rejection of the apparent inevitability of globalization in its present polarising form is particularly prophetic - instead he asserts the need for each society to negotiate the terms of its inter-dependence with the rest of the global economy. A landmark work by a key contemporary thinker.
Keywords: Capitalism